Brief psychosocial interventions improve quality of life of patients receiving palliative care: A systematic review and meta-analysis. (March 2019) - Warth, Marco; Kessler, Jens; Koehler, Friederike; Aguilar-Raab, Corina; Bardenheuer, Hubert J.; Ditzen, Beate
Background: Patients with a terminal disease report a high need for psychosocial and spiritual support. Previous literature reviews on psychosocial interventions in palliative care were restricted to certain subtypes of techniques, included a wide range of patients, conditions, and settings, or required a number of sessions unrealistic to be achieved in patients nearing the end of their lives. Aim: The aim of this study was to review and synthesize the evidence on brief psychosocial interventions (i.e. four sessions or less and less than 21 days) for patients receiving palliative treatment. Design: We performed a systematic review and meta-analysis in accordance with standard guidelines and a pre-registered protocol (PROSPERO: CRD42018082713). Data sources: Electronic databases, journals, and references were searched for controlled clinical trials. We used the Cochrane criteria to assess the risk of bias within studies. Results: In total, 15 studies met the eligibility criteria and reported the effects of 17 interventions and a total of 1248 patients. The most frequently used techniques were life review techniques and music therapy. After exclusion of outliers, psychosocial interventions showed to be superior with regard to the improvement of quality of life (effect size = 0.36, confidence interval = 0.08 to 0.64), and the reduction of emotional (effect size = −0.51, confidence interval = −0.77 to −0.26) and existential distress (effect size = −0.40, confidence interval = −0.71 to −0.07) compared to the control groups. Conclusion: Brief psychosocial interventions can improve clinically relevant health outcomes and should therefore be made available for patients receiving palliative care.